Preliminary studies of fourier analysis for some climate data that influences heat transfer in building envelope / Masriah Hj Awang and Zainazlan Md Zain - Awang, Masriah; Md Zain, Zainazlan (Institute of Research, Development and Commercialization (IRDC), 2007)
Energy utilization in buildings continues to increase as quality of life increases. Buildings are built in an environment and the climate surrounding a building is a factor that will influence the amount of energy for the building services. The higher the thermal stress due to the external condition, the higher the energy needs to provide the same building service. This paper discusses the different types of analyses of climate for Subang. The climate data were calculated using the monthly hourly averaged. Then the least squares method and fast Fourier transform via MATLAB were explored in order to get some important information. Overall, the temperature distribution, solar radiation, relative humidity distribution, rainfall distribution, wind-speed distribution and pressure distribution were presented. The least square polynomial of degree four and ten were chosen to represent the climate data. The least square error and the norm of the residual for these two polynomials were the smallest among other polynomials. The coefficients of determination were also calculated. The Fast Fourier Transform (FFT) from MATLAB toolbox was also used to disclose the pattern of the climate data. The FFT shows the Fourier coefficient on the complex plane. A peridogram of power versus frequency and a peridogram of power versus period were obtained for the climate data via MATLAB. These studies reveal the patterns that need to be considered for optimum energy utilization in buildings.